The relationship between investor flows and returns on the Egyptian stock exchange - El-Batrawy, Manar K. (AUC Knowledge Fountain, 2015)
This paper examines the relationship between equity flows by domestic, Arab and foreign investors and returns in the Egyptian Stock Exchange (EGX) using daily investor flows data for the period from January 2004 till December 2013.The sample consists of aggregate buy/sell investor flows by individual and institutional investors of the three main categories (domestic, Arabs and foreigners). A vector-autoregression tool was used to analyze the data through two different regressions, one for the impact of returns on flows, and the other for the impact of flows on returns. The main key findings of the flows model were that domestic, Arab and foreign investors exhibit positive feedback trading in their buy and contrarian in their sell trades, except for domestic institutional trades, who showed no significant trading behavior. For the return model, the results were that purchases of domestic institutions, domestic individuals, Arab institutions, Arab individuals, foreign individuals are strongly positively related to returns, while foreign institutions showed no significance with returns in any manner. As for the sales, domestic individuals, Arab institutions, Arab individuals, foreign institutions and foreign individuals exert price pressure, which causes contemporaneous effect on returns, while domestic institutions showed no significance with returns in any manner. Interestingly enough, the trend reverses during crisis periods.